CONSTRUCTION OF A GENERAL SOLUTION OF ONE CLASS OF LINEAR DIFFERENCE EQUATIONS OF ORDER n - Turaev H.; Khurramov N.; Karasakalov R (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Using the method of sequential integration, it is possible, as in the case of a homogeneous equation [3], to construct various kinds of partial solutions to equation (1).